Complications, Length of Hospital Stay, and Cost of Care after Surgery for Pyogenic Spondylodiscitis - Abboud, Tammam; Melich, Patrick; Scheithauer, Simone; Rohde, Veit; Schatlo, Bawarjan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background Infectious Spondylodiscitis is a heterogeneous disease usually affecting a fragile patient population with multiple comorbidities. Therefore, surgical and medical complications are important considerations before initiating treatment.Methods This retrospective analysis included data of 218 patients who underwent surgical treatment for pyogenic Spondylodiscitis between 2008 and 2016. Groups were divided into length of hospital stay (LOS) (group I ≤21 days and group II>21 days). Analysis included patient age, gender, Charlson comorbidity index, smoking, obesity, osteoporosis, colonization with multidrug-resistant bacteria, preoperative neurologic deficit, pre- and postoperative inflammation markers (CRP and WBC), duration of surgery, number of operated segments, vertebrectomy, and postoperative medical and surgical complications. The case value for each patient expressed in Euro was retrieved from hospital records and included in the analysis.Results Duration of stay after surgical treatment of Spondylodiscitis was ≤21 days (range: 4–21 days; mean: 16 days) in 41% of patients and >21 days (range: 22–162 days; mean: 41 days) in 59% of the patients. Multivariate analysis showed that both medical complications (odds ratio [OR]: 2.62; 95% confidence interval [CI]: 1.24–5.56; p=0.012) and surgical site infection (OR: 6.04; 95% CI: 2.35–15.51; p<0.001) were independently associated with a long hospital stay. Case values averaged at €21,667±1,579 (minimum: €2,888; maximum: €203,802) and correlated significantly with the length of hospital stay (Pearson's correlation coefficient: 0.681; p<0.05). The occurrence of a postoperative complication increased the cost of care significantly from €17,790 to 24,527 on average (p=0.025).Conclusions This study provides benchmark data for patients treated surgically for Spondylodiscitis. Surgical site infection and medical complications are the main drivers of prolonged hospital stays and cost of care.
Keywords: Spondylodiscitis; hospital-associated infection; osteomyelitis; spondylitis; epidural abscess